An In Silico Approach for Identification of P20 Candidate using Bioinformatics Tool - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Parthenium hysterophorus is a species of flowering plant in the family Asteraceae, locally known as carrot grass, congress grass, or Gajar Ghas. Objective: The study was aimed to investigate which orthologues of P. hysterophorus genes that might encode the P20 protein. Methods: Low-abundance proteins were found after fractionating P. hysterophorus leaf proteins in polyethylene glycol. Samples treated at −80°C shortened the time needed for protein to precipitate to 2 h. In addition, sonication was employed to remove non-protein impurities, which elevated protein solubility and enhanced MALDI-TOF mass spectrometry for protein identification. Results: Tryptic digest of purified protein revealed that the predicted size of the protein is 20kDa by MALDI-TOF and identification of peptides present in the P20 protein by peptide sequence analysis. Conclusion: This study describes how a combination of bioinformatics and proteomics approaches led to the identification of novel P20 candidates.